Service specification for senior care workers with traditional Chinese medicine specialty - Qi Zou; Qin Tang; Lei Wang; Jiawei Geng; Baofeng Deng; Zhen Yu; Ayue An; Lixin Wei; Xiaoying Tong; Peijing Rong (Science of Traditional Chinese Medicine)
Abstract. Senior care workers specializing in traditional Chinese medicine (TCM) healthcare have become an indispensable force in institutional care, community care, and home care. The first Chinese nursing service team aimed to improve the health of the elderly by providing continuous services for physical and mental well-being, disease prevention, physical amelioration, and overall health enhancement using TCM concepts, methods, and technologies. The primary purpose of formulating this TCM health and elderly care worker service specification was to standardize services within the TCM elderly care industry, ensuring that the elderly receive better health and elderly care services supported by technical expertise. This specification outlined the basic requirements for TCM health and elderly care workers, including standards for service content, service quality control, service evaluation, and improvement. It primarily focused on the content and requirements of TCM health and elderly care services, such as constitution identification, life care, acupoint healthcare, and TCM auxiliary nursing for elderly individuals with chronic diseases. This specification is applicable to TCM health and elderly care personnel at various levels of hospitals and healthcare institutions and is noted for its strong applicability and effectiveness.